Energopolitics: Wind and power in the Anthropocene. Dominic Boyer - Escoto Mora, Iván Ismael (Alteridades, 2022)
Reseña del libro: Boyer, Dominic (2019). Energopolitics: Wind and power in the Anthropocene. Durham-London. Duke University Press.